2008
DOI: 10.1177/2156759x0801100505
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Holland Vocational Personality Types: Implications for School Counselors

Abstract: The study in this article examined gender and ethnic differences in the development of Holland (1997) personality types among inner-city adolescents. Results showed gender but not ethnic differences in vocational personality types and their predictors, and suggest different pathways to the development of these types for boys and girls. Suggestions are highlighted for providing school counseling interventions based on study results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Saha (Holland, 1997). The adherents of this tradition expected boys and girls to have different career expectations because of the contents of their socialisation experiences, that is, through the cultivation of typically feminine and masculine traits and personality differences (Tang, Pan, & Newmeyer, 2008;Turner, Conkel, Starkey, & Landgraf, 2008). The social allocation perspective has focused on social structural constraints, that is, race, ethnicity, institutional settings, including features of particular schools or school systems and labour market characteristics.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Saha (Holland, 1997). The adherents of this tradition expected boys and girls to have different career expectations because of the contents of their socialisation experiences, that is, through the cultivation of typically feminine and masculine traits and personality differences (Tang, Pan, & Newmeyer, 2008;Turner, Conkel, Starkey, & Landgraf, 2008). The social allocation perspective has focused on social structural constraints, that is, race, ethnicity, institutional settings, including features of particular schools or school systems and labour market characteristics.…”
Section: Introductionmentioning
confidence: 98%
“…Sikora and L.J. Saha typology (1997), medicine typifies ''investigative'' occupations, while law is a typical ''enterprising'' occupation, and both are usually assumed to be typical boys' choices (Turner et al, 2008). But law and medicine here come across as areas of employment that attract both boys and girls in different cultural and economic contexts.…”
mentioning
confidence: 98%
“…For gender differences in self-estimated abilities using Holland Theme abilities clusters as the measurement strategy, little empirical work has been done. However, in one reported study, researchers found that multiethnic urban adolescent boys have greater self-estimated abilities for R and I careers and girls have greater self-estimated abilities for A and S careers (Turner et al, 2008). Because associations between corresponding Holland Theme interests and self-estimated abilities are higher than between noncorresponding interests and abilities (ACT, 2009), one could assume that gender differences among Holland Theme self-estimated abilities would be similar to those found among interests.…”
mentioning
confidence: 90%